2020
DOI: 10.1002/jcla.23595
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative monocyte‐to‐HDL‐cholesterol ratio predicts early recurrence after radiofrequency maze procedure of valvular atrial fibrillation

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Canpolat et al have found that elevated pre-ablation MHR is associated with AF recurrence after cryo-catheter ablation after a mean follow-up of 20.6 ± 6.0 months [21]. Another study has found that higher pre-procedure MHR levels are independently associated with a significantly elevated risk of early AF recurrence after radiofrequency maze [22]. Suzuki et al [23] have observed that the proportion of CD14 + + CD16 + monocytes in peripheral blood is significantly higher in patients with AF than controls, and that peripheral blood CD14 + + CD16 + intermediate type monocytes may be closely associated with the pathogenesis of AF.…”
Section: Discussionmentioning
confidence: 99%
“…Canpolat et al have found that elevated pre-ablation MHR is associated with AF recurrence after cryo-catheter ablation after a mean follow-up of 20.6 ± 6.0 months [21]. Another study has found that higher pre-procedure MHR levels are independently associated with a significantly elevated risk of early AF recurrence after radiofrequency maze [22]. Suzuki et al [23] have observed that the proportion of CD14 + + CD16 + monocytes in peripheral blood is significantly higher in patients with AF than controls, and that peripheral blood CD14 + + CD16 + intermediate type monocytes may be closely associated with the pathogenesis of AF.…”
Section: Discussionmentioning
confidence: 99%
“…In 2004, for the first time, increased MHR was found to be strongly associated with an elevated risk of cardiovascular events in patients with chronic kidney disease ( 44 ). Moreover, MHR is clinically important in predicting both early recurrence and late recurrence of AF after catheter ablation ( 11 , 45 , 46 ). Meanwhile, MHR was found to be significantly associated with the organism’s left atrial size, CRP, and BNP levels ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…MHR, a ratio of monocyte count to HDL, is a novel serological marker of inflammatory and oxidative stress. MHR was found to be an independent risk factor for recurrent paroxysmal atrial fibrillation after cryoablation, with a sensitivity of 89% and specificity of 54% [ 11 ]. The results of this study showed that MHR was an independent risk factor for late recurrence of nonvalvular AF after catheter ablation, with a cutoff value of 0.5629, corresponding to a sensitivity of 83.1% and a specificity of 79.2%.…”
Section: Discussionmentioning
confidence: 99%